PENGGUNAAN TEKNOLOGI VIRTUAL REALITY DALAM PENDIDIKAN KEPERAWATAN JIWA : LITERATURE REVIEW - Deborah Ferdinanda Lumenta (Nursing Arts, 2021)
Introduction: In the era of industrial revolution 4.0, distance learning has a strategic role for spreading and equity in higher education, including nursing science. Triggered by the COVID 19 pandemic, nursing education needs to innovate how to achieve the competency without direct contact with patients. This study aimed at exploring the virtual reality method in nursing education, moreover in mental health nursing. Method: The study design is a literature review, using Pubmed as the search engine, continued with literature search from the selected articles, using the following key words: nursing education, virtual reality, competency; and nursing education, virtual reality, and mental health. We selected only English and articles of the recent 10 years Result: Eight articles were selected using the two sets of key words, consisted of 5 articles about nursing education and 3 articles were more on mental health nursing education. The study designs were varied from RCT, review and scoping review, descriptive study, and qualitative study. The context were undergraduate and postgraduate students.. Conclusion: Virtual reality is one candidate in nursing education, especially in mental health nursing education to improve competency among nursing student. Keyword: nursing education; virtual reality; mental health.